PENGARUH SISTEM PENGENDALIAN MANAJEMEN DAN INFORMASI AKUNTANSI LINGKUNGAN PADA PERUSAHAAN MANUFAKTUR BER-ISO 14000 - Handayani, Dwi; Wibisono, Haris (Widya Warta, 2014)
The purpose of this study was to investigate the influence of quality management control systems (quality goals, quality feedbacks and quality incentives) and environmental accounting on quality performance. The data used were collected from production managers of manufactur companies with ISO 14000. The data were obtained via mail survey on 414 questionnaires. The questionnaires which were relevant to the analysis were 46 in number. The analysis was conducted using SPSS ver. 12.The results showed that (1) communication intensity of quality goal toward the labourers was not significant to qualiy performance, (2) the frequency of quality feedback had a positive relationship with quality performance, (3) the improvement of incentives concerning quality had a positive relationship with quality performance, and (4) the implementation of environmental accounting had a positiverelationship with quality performance.